Biologi dan Peranan Aedes albopictus (Skuse) 1894 sebagai Penular Penyakit - Hasan Boesri (Loka Litbang Kesehatan Pangandaran, 2011)
Abstracts. Behavior of the mosquito Aedes albopictus is generally resting outside the homewith the brood in a natural or artificial containers protected from sunlight.Human biting activity between the hours of 9:00 to 11:00 and between the hours of 17:00 to18:00 inside and outside the home. The period of rest after sucking the blood 4-5 days and isready to lie. Habitat or the environment that most coveted of this mosquito is a forest or gardenwith temperatures of 24-30 º C. eggs hatch after 4-5 days with a temperature of 24-30 ºC, the eggs usually form clusters of 49-60 eggs Larvae and pupae usually found in containers,pieces of bambo containing water. The period of the larvae to adults between 20-25days. The spread of Ae albopictus mosquitoes from Africa, India, Pakistan, Sri Lanka, Thailand,Malaysia, Vietnam, Papua New Guinea, northern Australia, and Indonesia. Role indisease transmission is a secondary vector or as the primary vector of dengue hemorrhagicfever. On viral diseases that attack the nerves like encephalistis Japanese, Western or Easternencephalistis, and Chikuguya has been demonstrated by laboratories, as well as on animaldiseases caused by Dirofilaria immitis agent, Plasmodium lophurae, P. gallinaceum, andP. fallax.